Latent categories and their influencing factors of frailty change among community-dwelling older adults in Ma′anshan city: a 5-year follow-up study - Tengfei LI; Yuting LIANG; Yeke HE; Qirong QIN; Mengmeng WANG; Fen HUANG; Yehuan SUN; Jie LI (Zhongguo gonggong weisheng)
ObjectiveTo investigate the latent categories and influencing factors of frailty change over time among elderly residents in Ma′anshan city, Anhui province, and to provide a reference for the development of prevention and control measures against the onset and progression of frailty in this population. MethodsA multistage random sampling method was used to recruit 3 476 community-dwelling adults aged ≥ 60 years from three districts of Ma′anshan city. Baseline data were collected through face-to-face interviews (December 2016-March 2017) using standardized instruments: a self-developed questionnaire, the Scale of Elderly Self-neglect (SESN), the Psychological Stress Resilience Quotient Scale, the Social Support Scale (both validated by Chinese researchers), and the Frailty Index to assess frailty status. Follow-up surveys were conducted in December 2018 and December 2021. Among the initial cohort, 2 495 participants completed all three surveys and were included in the final analysis. Latent class analysis (LCA) identified distinct trajectories of in frailty over time, while multinomial logistic regression identified key influencing factors. ResultsAmong the participants included in the analysis, three latent categories of change in frailty during the observation period were identified: improvement, progression, and early fluctuation, with percentages of 534 (21.4%), 188 (7.5%), and 1 773 (71.1%) participants, respectively. The results of multinomial logistic regression analyses (with the improvement group as the reference) revealed the following significant baseline factors influencing membership in either the progression or early fluctuation groups: increased odds of being in the progression or early fluctuation groups were associated with age ≥ 75 years, annual or occasional physical examinations (occasional examinations significant only for the progression group), occasional or regular physical activity (significant only for the early fluctuation group), history of falls in the past year, self-neglect, and central obesity; whereas decreased odds of being in either group were associated with average monthly income of 2 000 - 4 999 Chinese yuan, living alone (significant only for the progression group), moderate or higher self-rated work intensity, alcohol consumption, and high psychological resilience scores. ConclusionsThe main latent category of frailty status among community-dwelling older adults in Ma′anshan city was early fluctuation. Age, average monthly income, living alone, self-reported work intensity, alcohol consumption, physical examination status, physical activity, falls in the past year, self-neglect, central obesity, and psychological resilience score were the main influencing factors of latent categories of frailty among the elderly.